About some issues of victimological prevention of fraud - Ozbekov, D.O.; Mashabaev, A.Zh.; Siubayeva, N.Zh. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2022)
Fraud, traditionally regarded in the history of law as the fraudulent acquisition of someone else’s property, is characterized by the emergence of new areas and methods that do not fit into the standard framework of the Criminal Code. Illegal acts in the field of high technology, investment, banking, insurance, etc., are qualified under the general rule of “Fraud”. The purpose of the study is to develop recommendations for improving victimological measures to combat fraud. During the study, general scientific and private methods and techniques were used: historical, legal, logical, the study of special literature, analysis, and generalization of the obtained data. The authors, examining the characteristics of victims that cause their victimization, reveal the content side of the mechanism of fraudulent actions. Using official statistics data, the analysis of the spheres and methods of fraud, the use of computer technology in the commission of fraudulent actions are carried out. Based on the analysis of the most common ways of committing fraud, victim-dangerous situations, and the properties of its potential victims, the authors formulated measures of victimological prevention of this crime. Among the promising directions in scientific and practical terms, constant informing of the population about new methods of deception, updating of practical tips on “How to protect yourself from fraudsters”, increasing the level of legal culture of citizens are proposed. These measures will create a model of human interaction with other people, society and the environment, which will lead to a reduction in the number of possible victims of fraudsters.
Алаяқтықтың виктимологиялық алдын алудың кейбір сұрақтары туралы
О некоторых вопросах виктимологической профилактики мошенничества
Keywords: fraud; behavior of a crime victim; specific victimization; recognition and prevention of a victim-threatening situation; preventive impact